Developing national systems of innovation university-industry interactions in the global south - Albuquerque, Eduardo da Motta; Suzigan, Wilson; Kruss, Glenda; Lee, Keun 1960- (Edward Elgar Publishing International Development Research Centre, 2015)
'What is similar and what is different about the relationships between how universities and public laboratories interact with firms in developing, as contrasted with advanced, industrial economies? How do these differences reflect and support the differences witnessed in on-going innovations? This book is the first large-scale report on these matters, and their implications for policy in developing countries.'--From the foreword by Richard R. Nelson, Columbia University, US. Interactions between firms and universities are key building blocks of innovation systems. With a focus on developing countries, this book presents novel comparative research spanning three continents. The result is a more universal and dynamic view of the shaping and reshaping of interactions between firms and universities within different countries in various stages of development. Through expert contributions, a combination of empirical investigations and theoretical discussion is presented, existing studies on innovation systems are quantified and further avenues of research suggested. Readers will establish a more universal understanding of the vibrant relationship between firms and universities, and how this affects innovation for the future. Scholars of innovation, evolutionary economics, science and technology studies, and development studies will find the original research to be of great value. This book will also appeal to public research organizations and policy makers--Back cover.